Teaching Collocations and Academic Phrases with Corpus Linguistics: Applications for Specific and Academic Contexts - Misnawati, Misnawati; Tahir, Saidna Zulfiqar Bin; Sibali, Alwi; Anwar, Widya Pertiwi; Basri, Nurfajriah; Bahtiar, Hikmanisa (Innovations in Language Education and Literature, 2025)
This study explores the integration of the Corpus of Contemporary American English (COCA) in teaching academic collocations and phrases in English for Specific and Academic Purposes (ESP/EAP) settings. Conducted with 15 first-semester undergraduate students in Indonesia, the six-week classroom-based action research employed corpus-based instructional tasks to develop students’ lexical awareness and academic language proficiency. Data were collected through classroom observations, student writings, questionnaires, and semi-structured interviews. The findings show notable improvement in students’ use of academic collocations and discipline-specific phrases, reflected in increased accuracy and fluency in both writing and speaking. Learners reported that COCA supported them in identifying more natural and context-appropriate word combinations, boosting their confidence and academic expression. Initial challenges with the COCA interface and corpus navigation were mitigated through instructional scaffolding. Over time, students demonstrated increased autonomy and began using COCA for independent and collaborative learning. The study affirms the pedagogical value of corpus linguistics for novice ESP learners and highlights the importance of technical and teacher support in integrating corpus tools into curriculum design.